An Assessment of Dialysis Provider's Attitudes towards Timing of Dialysis Initiation in Canada. Issue 1 (7th April 2014) - Mann, Bikaramjit S; Manns, Braden J; Dart, Allison; Kappel, Joanne; Molzahn, Anita; Naimark, David; Nessim, Sharon J; Soroka, Steven; Zappitelli, Michael; Sood, Manish M
Background: Physicians' perceptions and opinions may influence when to initiate dialysis. Objective: To examine providers' perspectives and opinions regarding the timing of dialysis initiation. Design: Online survey. Setting: Community and academic dialysis practices in Canada. Participants: A nationally-representative sample of dialysis providers. Measurements and Methods: Dialysis providers opinions assessing reasons to initiate dialysis at low or high eGFR. Responses were obtained using a 9-point Likert scale. Early dialysis was defined as initiation of dialysis in an individual with an eGFR greater than or equal to 10.5 ml/min/m 2 . A detailed survey was emailed to all members of the Canadian Society of Nephrology (CSN) in February 2013. The survey was designed and pre-tested to evaluate duration and ease of administration. Results: One hundred and forty one (25% response rate) physicians participated in the survey. The majority were from urban, academic centres and practiced in regionally administered renal programs. Very few respondents had a formal policy regarding the timing of dialysis initiation or formally reviewed new dialysis starts (N = 4, 3.1%). The majority of respondents were either neutral or disagreed that late compared to early dialysis initiation improved outcomes (85–88%), had a negative impact on quality of life (89%), worsened AVF or PD use (84–90%), led to sicker patients (83%) or was cost effective (61%). Fifty-seven percent of respondents felt uremic symptoms occurred earlier in patients with advancing age or co-morbid illness. Half (51.8%) of the respondents felt there was an absolute eGFR at which they would initiate dialysis in an asymptomatic patient. The majority of respondents would initiate dialysis for classic indications for dialysis, such as volume overload (90.1%) and cachexia (83.7%) however a significant number chose other factors that may lead them to early dialysis initiation including avoiding an emergency (28.4%), patient preference (21.3%) and non-compliance (8.5%). Limitations: 25% response rate. Conclusions: Although the majority of nephrologists in Canada who responded followed evidence-based practice regarding the timing of dialysis initiation, knowledge gaps and areas of clinical uncertainty exist. The implementation and evaluation of formal policies and knowledge translation activities may limit potentially unnecessary early dialysis initiation.